Can We Define Termination Of Resuscitation Criteria In Out-Of-Hospital Hanging?. (2nd January 2019) - Escutnaire, Joséphine; Ducrocq, François; Singier, Allison; Baert, Valentine; Babykina, Evgéniya; Dumont, Cyrielle; Vilhelm, Christian; Marc, Jean-Baptiste; Segal, Nicolas; Wiel, Eric; Mols, Pierre; Hubert, Hervé; et al.
Abstract: Objective: Survival rate of cardiac arrest due to hanging (H-CA) victims is low. Hence, this leads to the question of the utility of resuscitation in these patients. The objective was to investigate whether there are predictive criteria for survival with a good neurological outcome or predictive criteria for non-survival or survival with a poor neurological outcome enabling us to define the termination of resuscitation rules in these patients.Methods: Between July 1, 2011 and January 1, 2016, we included 1, 689 out-of-hospital cardiac arrests due to hanging. We compared the characteristics of survivors with a good neurological outcome at day 30 with the others.Results: The study population was mainly composed of males with a median age of 48 [37–60]. The overall survival was 2.1%, among which 48.6% had a good neurological outcome. Survivors benefited more often from immediate basic life support than the rest of the subjects, which was corroborated by the shorter no-flow durations. We did not record any difference in terms of advanced cardiac life support initiation frequency and technique between survivors with a good neurological outcome and the rest. Nevertheless, ACLS duration was longer in survivors with a good neurological outcome than in others.Conclusions: Basic life support (BLS) was the decisive criterion for 15/17 survivors. However, a detailed analysis showed 2 survivors presenting no BLS before the arrival of mobile medical teams and non-shockable rhythms who survived at day 30 with a good neurological outcome. These results lead us to consider that mobile medical team intervention and ACLS attempt are not futile, and the benefit justifies the cost. Thus, we cannot define any rule for the termination of resuscitation.